EFFECT OF FLUOXETINE ON THE SEXUAL BEHAVIOUR OF DROSOPHILA MELANOGASTER - Nazari, Mansour (Journal of Postgraduate Medical Institute, 2011)
Objective: Antidepressant drugs are administered in appropriate doses to get rid of depression. Most of these drugs have adverse effects on sexual function. Selective serotonin reuptake inhibitors (SSRIs) are antidepressants that cause sexual dysfunction. The effect of this drug on the sexual behaviour of Drosophila melanogaster is studied here. Methodology: The male, female and both treated groups were used. The effect of fluoxetine (FLX) on the sexual behavioural elements such as, orientation, tapping, wing vibration, scissoring, licking, circling, extruding and decamping were observed. The F1 and F2 progeny obtained from inbreeding of the above combinations were also used for observation. Three sub lethal concentrations (0.02, 0.04 and 0.06%) were administered by larval feeding method Results: Most of the male courtship acts and the non-receptive behaviour of females are affected by treatment of antidepressant drug in parents' generation. Sexual behaviour elements of male and female were insignificant in F1 and F2 progeny. Conclusion the progeny. Therefore, the author is of the opinion that low concentrations of these drugs could be used by man to get rid of depression. : The LC and concentrations used are very high. Furthermore, these drugs have no effect on